AGREEMENT BETWEEN CLINICAL FEATURES OF SCIATICA AND 3.0T MAGNETIC RESONANCE IMAGING FINDINGS - Mubashar, Saman; Mudassar, Tasmia; Bajwa, Beenish; Bajwa, Mudassar Ahmed; Bajwa, Mubashar Ahmed; Bazaz, Aemen Shafqat (Pakistan Armed Forces Medical Journal, 2020)
Objectives: To determine agreement between clinical features of sciatica and 3.0 T magnetic resonance imaging findings. Study Design: Descriptive, cross-sectional study. Place and Duration of Study: Department of Orthopedics, Combined Military Hospital Rawalpindi, from Nov 2017 to May 2018. Methodology: A total of 90 patients with low back pain radiating to one or both lower limbs and age 25-75 years of either gender were included. Patients with tumors of spine or vertebrae, trauma to spine, Pott’s disease and previous spinal surgery were excluded. Patients with clinically diagnosed sciatica were taken for magnetic resonance imaging on a 3.0 T magnetic resonance imaging console and images of lumbosacral spine were obtained by a qualified magnetic resonance imaging technician. The images were transferred to computers on reporting station and findings analyzed on vitrea. Reports were prepared according to the findings of magnetic resonance imaging. Agreement was measured if clinical features were positive (positive straight leg raise test) and magnetic resonance imaging showing any feature of disc herniation, disc prolapse and neural foramen narrowing. Results: Mean age was 53.11 ± 8.13 years. Out of these 90 patients, 46 (51.11%) were males and 44 (48.89%) were females with ratio of 1.1:1. In my study, numbers of observed agreements were 78 (86.67% of the observations) with Kappa value of 0.717 (95% confidence interval: from 0.568 to 0.865). The strength of agreement between clinical features of sciatica and 3.0 T magnetic resonance imaging findings is considered to be ’good’. Conclusion: This study concluded that there is a good agreement between clinical features of sciatica and 3.0 T magnetic resonance imaging findings. Careful clinical evaluation will help the clinicians for avoiding unnecessary magnetic resonance imaging in patients with sciatica.